2010
DOI: 10.2514/1.j050021
|View full text |Cite
|
Sign up to set email alerts
|

Boundary-Layer Transition on Broad Cones rotating in an Imposed Axial Flow

Abstract: We present stability analyses for the boundary-layer flow over broad cones (half-angle ψ > 40• ) rotating in imposed axial flows. Preliminary convective instability analyses are presented that are based on the Orr-Sommerfeld equation for a variety of axial-flow speeds. The results are discussed in terms of the limited existing experimental data and previous stability analyses on related bodies. The results of an absolute instability analysis are also presented which are intended to further those by Garrett & P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 29 publications
9
24
0
Order By: Relevance
“…From the study by Kobayashi et al (1983), it is found that the number of vortices around the circumference at an axial location is always greater than or equal to 8. Similar results have also been reported in the theoretical study by Garrett et al (2010), where they performed linear stability analyses on the range of broad cones (half angles • < < 90 • ). They observe that n decreases with increasing S but stays n ≥ 8 even at S → ∞ .…”
Section: Physical Admissibility Of Pod Modessupporting
confidence: 86%
“…From the study by Kobayashi et al (1983), it is found that the number of vortices around the circumference at an axial location is always greater than or equal to 8. Similar results have also been reported in the theoretical study by Garrett et al (2010), where they performed linear stability analyses on the range of broad cones (half angles • < < 90 • ). They observe that n decreases with increasing S but stays n ≥ 8 even at S → ∞ .…”
Section: Physical Admissibility Of Pod Modessupporting
confidence: 86%
“…This crucial difference motivates separate publication of the two cases and a preliminary Orr-Sommerfeld analysis of the rotating-cone boundary layer is presented in Ref. 4.…”
Section: Discussionmentioning
confidence: 99%
“…18 and all following laminar-flow investigations, the incompressible study presented in this paper can be considered as a preliminary investigation into how relevant instability analyses are to the design of CVD processes. This paper is related to the theoretical investigations of Garrett and Peake, 21 recently revisited by the current authors, 4 which consider the absolute instability of the boundary-layer flows over a family of cones rotating within imposed axial flows. There the rotating disk is considered as a special case of cone with half-angle 90…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Theoretical studies on the convective instabilities associated with the spiral vortices were undertaken by Kobayashi and co-workers [32,35]. Using a new base flow model, Garrett et al [36] improved upon the earlier linear stability calculations presented by Garrett and Peake [8] for rotating-cones in a uniform axial flow. However, results were unchanged for those boundary layers with a zero axial flow.…”
Section: Introductionmentioning
confidence: 99%